Gender and strategy use in proportional situations: an Icelandic study - Steinthorsdottir, Olof B.; Sriraman, Bharath (NOMAD Nordic Studies in Mathematics Education, 2007)
This study was conducted to investigate the influence of contextual and number structures on individuals’ use of strategies in solving missing value proportion problems, and to examine gender differences in strategy use. Fifty-three eighth graders in one school in Reykjavik, Iceland, participated in this study. Twenty-seven females and twenty-six males were individually interviewed as they solved sixteen missing value proportion problems. The problems represented four contextual structures. No gender differences were identified in the overall success rate. However, girls were more successful than boys in handling associated sets and symbolic problems, and boys were more successful than girls in part-part-whole problems. Moreover, the data suggest that the contextual structures influence females’ choice of strategy more than that of males.